Ustavno sodišče kot pozitivni zakonodajalec - Ribičič, Ciril (Podjetje in delo, 2015)
The proceedings, edited by Professor Allan D. Brewer-Carias bring together numerous national reports tackling questions whether and to what extent constitutional courts in their respective jurisdictions act as positive legislators. The publication lacks a report from Slovenia. It is the goal of this article to fill this gap. The case law of the Constitutional Court of the Republic of Slovenia since the adoption of the Constitution of the Republic of Slovenia 25 years ago demonstrates a surprising number of cases which interfere with the competences of the legislator. The author warns that the comprehensive analysis of the Constitutional Court's case law is not his intention. He does present, however, some cases in which distinct circumstances had acted as an incentive for the Court to rule innovatively. In some of them the Constitutional Court took on the roles of the Parliament and some other state bodies (State Election Commission and Judicial Council). In some rulings - due to disrespect of its own rulings - it gradated sanctions in a unique way, in others it demonstrated acts of positive judicial activism developmentally interpreting the constitutional provisions on human rights and freedoms. In some rulings it acted against the limiting of the constitutional principles by the parliamentary and/or referendum majority etc. The author concludes by demonstrating the endeavours by the constitutional jurisprudence to give a theoretical meaning to the broadening of the competences and power of constitutional judiciary in the system of constitutional democracy. The author refers to proposals for narrowing the functions of constitutional courts and subjecting constitutional court judges to the parliamentary majority managed by the executive with the help of partitocracy.
Keywords: delitev oblasti; democracy; demokracija; odločanje; parlamenti; pravosodje; sodne odločbe; ustavna sodišča; zakonodaja